A Comparison of Drought-Tolerant Prairie Plants to Support Managed and Wild Bees in Conservation Programs. Issue 5 (24th July 2018) - Rowe, Logan; Gibson, Daniel; Landis, Douglas; Gibbs, Jason; Isaacs, Rufus
Abstract: In response to growing concerns surrounding pollinator health, there have been increased efforts to incorporate wildflower habitat into land management programs, particularly in agricultural systems dependent on bee-mediated pollination. While recommended plant lists abound, there is limited research on which plant species support the greatest bee abundance and diversity. In many farm settings, drought-tolerant plant species adapted to well-drained sandy soils are needed, since wildflower plantings are typically not irrigated. We used a common garden experimental design to evaluate 51 drought-tolerant native perennial plant species, and 2 non-native plant species in three regions of Michigan for their ability to support honey bees ( Apis mellifera L. (Hymenoptera: Apidae)) and wild bees. 1, 996 honey bees and 2, 496 wild bees were recorded visiting study plants. The wild bee community visiting plant species was dominated by Bombus spp. (Hymenoptera: Apidae) (25%), Halictus spp. (Hymenoptera: Halictidae) (23%), and Lasioglossum spp. (Hymenoptera: Halictidae) (16%). The number of honey bees and wild bees visiting study plants varied considerably, suggesting that bee groups have distinct preferences for plant species. Of the plant species assessed, Asclepias syriaca L. (Gentianales: Apocynaceae) (early season), Monarda fistulosa L. (Lamiales: Lamiaceae) (middle season), and Solidago speciosa Nutt. (Asterales: Asteraceae) (late season) were the three most attractive plant species to the entire bee community. Many other plants consistently attracted a high abundance of wild bees, honey bees, or both. Our results inform plant selection to support managed and wild bees as part of pollinator conservation programs in the Great Lakes region of the United States.